Purinergic Signalling: Therapeutic Developments - Burnstock, Geoffrey (Frontiers in Pharmacology, 2017)
Purinergic signalling, i.e., the role of nucleotides as extracellular signalling molecules, was proposed in 1972. However, this concept was not well accepted until the early 1990’s when receptor subtypes for purines and pyrimidines were cloned and characterised, which includes four subtypes of the P1 (adenosine) receptor, seven subtypes of P2X ion channel receptors and 8 subtypes of the P2Y G protein-coupled receptor. Early studies were largely concerned with the physiology, pharmacology and biochemistry of purinergic signalling. More recently, the focus has been on the pathophysiology and therapeutic potential. There was early recognition of the use of P1 receptor agonists for the treatment of supraventricular tachycardia and A2A receptor antagonists are promising for the treatment of Parkinson’s disease. Clopidogrel, a P2Y12 antagonist, is widely used for the treatment of thrombosis and stroke, blocking P2Y12 receptor-mediated platelet aggregation. Diquafosol, a long acting P2Y2 receptor agonist, is being used for the treatment of dry eye. P2X3 receptor antagonists have been developed that are orally bioavailable and stable in vivo and are currently in clinical trials for the treatment of chronic cough, bladder incontinence, visceral pain and hypertension. Antagonists to P2X7 receptors are being investigated for the treatment of inflammatory disorders, including neurodegenerative diseases. Other investigations are in progress for the use of purinergic agents for the treatment of osteoporosis, myocardial infarction, irritable bowel syndrome, epilepsy, atherosclerosis, depression, autism, diabetes, and cancer.